A new twist on an old idea: a two‐dimensional speckle tracking assessment of cyclosporine as a therapeutic alternative for heart failure with preserved ejection fraction. Issue 7 (5th December 2013) - Hiemstra, Jessica A.; Liu, Songtao; Ahlman, Mark A.; Schuleri, Karl H.; Lardo, Albert C.; Baines, Christopher P.; Dellsperger, Kevin C.; Bluemke, David A.; Emter, Craig A.
Abstract: We recently reported that mitochondrial dysfunction, characterized by increased mitochondrial permeability transition (MPT), was present in a translational swine model of heart failure with preserved ejection fraction (HFpEF). Cyclophilin D is a key component of the MPT pore, therefore, the purpose of this study was to test the efficacy of a novel cyclosporine (CsA) dosing scheme as a therapeutic alternative for HFpEF. Computed tomography (CT), two‐dimensional speckle tracking two‐dimensional speckle tracking (2DST), and invasive hemodynamics were used to evaluate cardiac function. CT imaging showed 14 weeks of CsA treatment caused eccentric myocardial remodeling (contrasting concentric remodeling in untreated HF animals) and elevated systemic pressures. 2DST detected left ventricular (LV) mechanics associated with systolic and diastolic dysfunction prior to the onset of significantly increased LV end diastolic pressure including: (1) decreased systolic apical rotation rate, longitudinal displacement, and longitudinal/radial/circumferential strain; (2) decreased early diastolic untwisting and longitudinal strain rate; and (3) increased late diastolic radial/circumferential mitral strain rate. LV mechanics associated with systolic and diastolic impairment was enhanced to a greater extent than seen in untreated HF animals following CsA treatment. In conclusion, CsA treatment accelerated the development of heart failure, including dilatory LV remodeling and impaired systolic and diastolic mechanics. Although our findings do not support CsA as a viable therapy for HFpEF, 2DST was effective in differentiating between progressive gradations of developing HF and detecting diastolic impairment prior to the development of overt diastolic dysfunction. Abstract : e00174 We recently reported that mitochondrial dysfunction, characterized by increased mitochondrial permeability transition (MPT), was present in a translational swine model of heart failure with preserved ejection fraction (HFpEF). Cyclophilin D is a key component of the MPT pore, therefore, the purpose of this study was to test the efficacy of a novel cyclosporine (CsA) dosing scheme as a therapeutic alternative for HFpEF. CsA treatment accelerated the development of heart failure, including dilatory LV remodeling and impaired systolic and diastolic mechanics. Although our findings do not support CsA as a viable therapy for HFpEF, 2DST was effective in differentiating between progressive gradations of developing HF and detecting diastolic impairment prior to the development of overt diastolic dysfunction.